Information sources and adoption of exclusive breastfeeding by rural mothers in Anambra state, South-eastern Nigeria (2016)
The rate of exclusive breastfeeding (EBF) remains very low in Nigeria, especially in rural areas, in spite of the spread of information on exclusive breastfeeding. Scholars have identified that adequate information about breastfeeding from information sources can enhance knowledge, attitude and practice among nursing mothers in rural communities. Although previous studies have focused mostly on adoption of EBF, no known studies have been carried out in relation to information sources and EBF among women in Anambra State, South-Eastern Nigeria. This study therefore investigated the influence of information sources on adoption of EBF among nursing mothers in Anambra State, Nigeria. A mixed mode cross sectional survey design was employed in carrying out the study among 211 respondents and 24 discussants comprising women with infants not more than 6 months and residing in the study communities. The results show that health officials (45.5%), radio (32.7%) and television (6.2%) were the main information sources through which respondents were exposed to EBF information. The findings also revealed that EBF practice was very low (25.6%) amdng the mothers and that health officials, faith- based organization (church) and friends were the sources of information that had significant influence on the mothers' adoption of EBF. Information from the FGD also revealed that certain factors act as barriers to the adoption of exclusive breastfeeding among the respondents. They include, among others, cultural beliefs and practices, the belief that breast milk is not enough, financial status, influence of mother, mothers-in-law and other family members and lack of knowledge about the harmful effects of suboptimal breastfeeding. The study established that, although health officials, radio and television are the main sources through which the nursing mothers receive EBF information, EBF information from community-based information sources are more effective in influencing rural nursing mothers to adopt EBF than the mass media. Also, certain factors hinder the adoption of exclusive breastfeeding. Hence, relevant organizations/agencies should utilize community-based information sources more than the mass media to increase the adoption of exclusive breastfeeding. Importantly, efforts should be made at addressing the barriers to the adoption of exclusive breastfeeding.